A STUDY OF SOCIAL AND ECONOMICAL FACTORS IN THE DEVELOPMENT OF CARDIOVASCULAR DISEASES WITH A SCREENING OF 4 TOWNS IN THE MOSCOW REGION - A. N. Britov; N. A. Eliseeva; A. D. Deev; S. A. Shalnova; T. S. Kolesnikova (Российский кардиологический журнал, 2001)
A study of social and economical factors in the development of cardiovascular diseases with a screening of 4 towns in the Moscow region.